Partisipasi dalam Sharing Economy Melalui Pendekatan Komunikasi - Prima, Luhtfiana; Anom Kumbara, A. A. Ngurah; Suwena, I Wayan (Sunari Penjor : Journal of Anthropology; Vol 5 No 1 (2021), 2021)
In the mid 20th century, tourism has been reached by technology, especially with the internet network. One of the changes that is the result of technology evolution is the developing model of production and consumption of goods and services, called the sharing economy.  One of the successful example of sharing economy technology that is currently popular with tourists is Airbnb.  The specific objective of this research is to understand and describe thoroughly the sharing economy and its implications for cross-cultural communication of hosts and guests in in North Kuta District.  Rhenald Kasali, Professor of FE UI said that "Sharing the economy is an attitude of participation in economic activities that creates value, independence and prosperity".  Deddy Maulana (in Darmastuti, 2013: 3) states that in a matter of communication, harmony is the meaning of conversation.  According to E.B Taylor, what is called culture is a form of method used to survive that is owned by certain individuals / groups and then passed on from generation to generation. The research method used in this research is a qualitative research.  The role of the host in giving an impression of local life is very important in order to create a good impression on the eyes of guests.  Interact and communicate with locals who help these guests at being able to see things from different point of view. With the role of the host in introducing local life to the guests, it will lead to an understanding in which generally everyone has different views about the world and culture in each community. When hosts and guests communicate, the other party hears different opinions, this, then, builds mutual respect, respect and compromise. For foreign guests, the cross-cultural communication created Broadens insight and understanding of political, religion and social status issues that affect the lives of local residents.